Reading for IELTS - Els Van Geyte (Tp. Hồ Chí Minh: Tổng hợp Tp. Hồ Chí Minh ; Công ty Nhân Trí Việt, 2021)
If your reading skills are preventing you from getting the score you need in IELTS, Collins Reading for IELTS can help. - Don’t let one skill hold you back - Features the types of questions used in the test such as identifying writers’ views or claims and completing summaries and tables - Exercises based on texts adapted from authentic sources - Exam tips and test practice in every unit plus a full practice paper at the back of the book - Build your vocabulary with the topic-based vocabulary work at the start of every unit - Essential IELTS vocabulary presented using Collins COBUILD dictionary explanations - Written by an experienced IELTS tutor